An exploratory analysis of organizational citizenship behaviour factor structure among employees in hotel industry / Shaiful Annuar Khalid and Hassan Ali - Khalid, Shaiful Annuar; Alias, Hassan (Universiti Teknologi MARA, Perlis, 2005)
Most of the literature on organizational citizenship behavior (OCB) was developed in the West, mainly North America. Not much is known about the meaningfulness and categories of OCB in other cultural environment such as Malaysia. This study investigates the dimensionality of OCB using a sample of hotel employees. Factors analysis of OCB items as rated by superiors revealed 5 dimensions, labeled as helping behavior, sportsmanship, conscientiousness, patience and civic virtue. Factor analysis of OCB items based on self-ratings (non manager employees) resulted in six dimensions, named as altruism, courtesy, conscientiousness, sportsmanship, effort expended and civic virtue. These results show that the forms of OCB seem to hold relatively well in another international context, although there are some differences.